ALTERNATIF PENYELESAIAN SENGKETA KLAIM ASURANSI DI BMAI DAN LAPS SJK - Simanjuntak, Jane Laura; Simanjuntak, Kornelius (Universitas Ekasakti, 2023)
This research analyses the efficiency, effectiveness and impact of the resolving insurance claims disputes by the newly established The Alternative Dispute Resolution of Financial Services Centre (LAPS SJK) since The Indonesia Insurance Mediation and Arbitration Centre (BMAI) was closed (liquidated) by the order of the Indonesia Financial Services Authority (OJK), and its task and function in resolving insurance claims disputes was transferred to LAPS SJK. Juridical research method is used in writing this research with secondary data. The result of this research shows resolving of insurance claims disputes at BMAI was more efficient and effective than at LAPS SJK. In 2021, the first year of operation of LAPS SJK, there were 10 financial disputes resolved at LAPS SJK, of which 2 cases were insurance claims disputes. There is a total number of 13.516 financial disputes received by LAPS SJK in 2021 waiting for resolution of which 177 are insurance claims disputes. The very low achievement was very disappointed and not in accordance with one of the principle in resolving disputes that is efficient and effective at LAPS SJK. There is a bad impact of the bad achievement of LAPS SJK to the good reputation of insurance industry in the insuring public and the society. This research suggests LAPS SJK: 1 to immediately do a crash programme for resolving the pending financial disputes; 2 to adopt the Ajudication resolution method that is the most efficient and effective in time resolving the financial disputes, as it has only two hearings or three the maximum in the experience of BMAI during its services. With the Ajudication, the thousand pending financial disputes can be hopefully resolved more quickly; 3 to improve its infrastructures including the number of hearing and meeting rooms for arbitration, Ajudication, and Mediation, human capital with good experience, capacity and expertise, and 4 to appoint a new managing director or head of LAPS SJK with good experience in ADR, capacity, expertise, strong leadership, and good tract record.